Penguatan Peran Guru dalam Pencegahan Diskriminasi dan Stigma Melalui Pendidikan GEDSI DI MIS TARBIYATUL ISLAMIYAH - Nailul Ulah Al Chumairoh Machfud; She Fira Azka Arifin; Febriarsita Eka Sasmita; Roidatus Shofiyah; Mirza Elmy Safira; Ita Ayu Wulandari (BAMALA Institute, 2024)
Through the GEDSI approach (Gender, Disability, and Social Inclusion), teachers can become agents of change in preventing the emergence of stigma against students from diverse backgrounds, including girls, students with disabilities, and those from other vulnerable groups. This community service program was carried out at MIS Tarbiyatul Islamiyah with the aim of strengthening teachers' capacity to understand and apply GEDSI principles in the learning process and social interactions at school. These activities were conducted through interactive training and simulations that encouraged teachers to recognize often-unnoticed forms of discrimination and to design inclusive and equitable learning approaches. The results of the program indicated an increased understanding among teachers of the importance of GEDSI mainstreaming and the emergence of a collective commitment to integrate these values into internal policies and classroom practices. This program contributed to the creation of a more inclusive, fair, and responsive madrasah environment that respects the diversity of students.